Subsidies, Land Size and Agricultural Output - Kyriazi, Foteini; Thomakos, Dimitrios D.; Rezitis, Antonis (Review of Economic Analysis, 2023)
In this paper we make a two-fold contribution. We first examine the impact of agricultural subsidies on Greece, using a detailed, micro-panel dataset for four years, 2008, 2010, 2012, and 2014. Our analysis is illuminating at least two aspects of subsidies: first, it suggests that an incentive scheme for promoting a larger farm size would have a probable positive effect on agricultural value-added; second, that subsidies today produce the larger impact on future value-added for the top two percentiles of the subsidy distribution. The adjacent contribution is the presentation of a new theoretical model on subsidies where we examine the impact of land size and taxes on them. We estimate the model’s hyperparameters, using Greek data from the FADN database. Our new theoretical results, combined with the empirical analysis on the first part, suggest that agricultural subsidies are of dubious economic value, in magnitude and effect, and distort the incentives for returns-to-scale and increased working hours in Greek agriculture.